2016
DOI: 10.3389/fpsyg.2016.00526
|View full text |Cite
|
Sign up to set email alerts
|

Treating Post-traumatic Stress Disorder in Patients with Multiple Sclerosis: A Randomized Controlled Trial Comparing the Efficacy of Eye Movement Desensitization and Reprocessing and Relaxation Therapy

Abstract: Objective: Multiple Sclerosis (MS) is a demyelinating autoimmune disease that imposes a significant emotional burden with heavy psychosocial consequences. Several studies have investigated the association between MS and mental disorders such as depression and anxiety, and recently researchers have focused also on Post-traumatic Stress Disorder (PTSD). This is the first study that investigates the usefulness of proposing a treatment for PTSD to patients with MS.Methods: A randomized controlled trial with patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 83 publications
(84 reference statements)
4
52
1
1
Order By: Relevance
“…A recent study by Carletto and colleagues () compared relaxation therapy to EMDR among patients with multiple sclerosis who were diagnosed with PTSD. Within‐group analyses revealed large effect sizes for both conditions on clinician‐assessed and self‐reported PTSD symptoms and between‐groups analyses revealed no differences by treatment condition.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A recent study by Carletto and colleagues () compared relaxation therapy to EMDR among patients with multiple sclerosis who were diagnosed with PTSD. Within‐group analyses revealed large effect sizes for both conditions on clinician‐assessed and self‐reported PTSD symptoms and between‐groups analyses revealed no differences by treatment condition.…”
Section: Resultsmentioning
confidence: 99%
“…(), included more male participants (64% and 55%, respectively). Four of the studies used ITT analyses (Carletto et al., ; Hinton et al., ; Markowitz et al., ; Vaughan et al., ), while the remaining used completer analyses (Marks et al., ; Taylor et al., ; Zucker et al., ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study of MS patients with posttraumatic stress disorder, the efficacy of two treatments including Eye Movement Desensitization and relaxation therapy was compared in two groups of patients. Results indicated that both methods were effective in reducing stress, anxiety, depression, and improving quality of life (Carletto et al., 2016). In another randomized controlled trial, Artemiadis and colleagues examined a stress management program that included progressive muscle relaxation and breathing techniques for relapsing–remitting MS patients.…”
Section: Discussionmentioning
confidence: 99%